Um modelo psicanalítico para pensar e fazer grupos em instituições - Castanho, Pablo de Carvalho Godoy (2012)
Psychologists and other professionals have been increasingly asked to conduct groups in various types of organizations: health and social services, schools, companies etc... On the other hand, several well respected group theories were designed for group work in private practice and are thus not prepared to properly address such organizational environments and demands. But beyond the technical dimension, the ethical principles of such work must be addressed. Based on a psychoanalytical perspective, our stand is that such groups should aim at promoting spaces where experiences, lived in social situations, can be appropriated by symbolization, and, at the same time, should contribute to organizational and social changes whenever excessive suffering is produced and reproduced. We believe that the psychoanalytical technique can guide us thru the reflection about how groups can achieve such goals. On these lines, this thesis general goal is to propose the basis for a psychoanalytical model which could comprehend every psychological related group practice in organizations and which offers parameters to both establishing group s pertinence to each organizational context and providing for a detailed discussion of its conduction. Our method is mainly theoretical in which Pichon-Rivière s concept of task is central as we take it as a touching stone that a group task must absolutely be aligned with the organizational primary task in all cases. We employ key concepts form René Kaës to bridge group and psychoanalysis, allowing for a comprehensive psychoanalytical debate. From this debate, the main elements of our model emerge. We take the learning operative group and the group with mediating objects (highlighting the Fotolanguage©, as discussed by Vacheret) as the two group strategies (settings) of reference to all of our work. We propose that the transference with the task can be independent from the transference with a group conductor and that it selectively attracts psychic elements connected to certain social dimensions. We approach the problem of interventions in the group in terms of transference with the task interpretations and uses of parameters (according to Eissler´s terminology). Towards the end of the thesis, we will present three group strategies discussed in supervisions which shall illustrate and dialog with our ideas. We can thus establish the foundations of what we call Task Centered Psychoanalytical Groups